Computer games as an expressive medium - Švelch, Jaroslav (Iluminace, 2012)
Introduction to the thematic block of articles dedicated to computer games as cultural artefacts. The text introduces the topic as a whole and the main ideas of the individual papers.
Keywords: computer games; gaming culture; gaming studios